Literasi Perempuan Digital Immigrant di Perdesaan - Oktiani, Hestin; Puspandari; Effendy, M.Yusuf; Rezeki, Fri; Ninggar, Emirullyta Harda (Wacana Publik, 2023)
Media consumption in large enough quantities, with a fairly frequent frequency and for a long enough duration can cause addiction in children and teenagers. Various services are available on the internet, this means that children and teenagers can stay on the internet for a long time. Therefore, parents need to have the knowledge and ability to supervise and regulate internet use among children and adolescents. Since the Covid 19 pandemic, the use of gadgets and the internet has become increasingly popular among children in both urban and rural areas. What is the condition of parents' knowledge and abilities regarding digital applications that can be used to monitor and regulate children's internet use is very important to know. This is thought to have an influence on how parents supervise or assist children and teenagers in internet use. This was researched using a quantitative approach. The method used was a survey method, with a population of mothers who had children attending junior high school in Pagelaran District, Pringsewu Regency. Of the 22 villages, 14 villages were selected as research locations, with a total of 212 mothers as respondents, taken purposively and modified snowball sampling. The data was processed and analyzed using percentage and tabulation formulas. The results of the study showed that there were still very few mothers in the villages. who have digital literacy skills and tools that can be used to supervise and regulate children's use of gadgets. Apart from that, literacy in digital tools is still minimal. This is based on the past cultural background of women/mothers in rural areas as digital immigrants. However, women/mothers in rural areas are aware of the negative impact that will occur on their children both physically and mentally if they use gadgets excessively and unwisely. Mothers have the desire to gain knowledge and have skills in using digital tools to monitor and regulate their children's use of gadgets.